Use of the Sport Concussion Assessment Tool 5 (SCAT5) in professional hockey, part 2: which components differentiate concussed and non-concussed players? - Bruce, J. M.; Thelen, J.; Meeuwisse, W.; Hutchison, M. G.; Rizos, J.; Comper, P.; Echemendia, R. J. (British Journal of Sports Medicine, 2021)
Objectives: To examine the utility of Sport Concussion Assessment Tool (SCAT5) subcomponents in differentiating physician diagnosed concussed players from controls.